GROUNDING MULTICULTURALISM IN INDONESIA - Sholikhudin, M. Anang (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan)
Indonesia is the largest archipelago in the world with over 17,000 islands, and also made up of various ethnic groups who have diverse customs and cultures, embracing different religions and beliefs, then pillars required in accordance with the conditions and needs in Indonesia. The enormous potential of this finding the right momentum to be the pride of the nation and of concern  the occurrence of inter-ethnic hostility, groups and religious differences that have an impact on the disintegration of the nation. Thus, insights multiculturalism needs to be understood and internalized together all layers of the nation to realize the great country and could be an example for world peace.